Dissolved rare earth elements in the Northwest Pacific: Sources, water mass tracing, and cross‐shelf fluxes - Cao, Axiang; Zhang, Jing; Zhang, Honghai; Chen, Zhaohui; Cui, Guanghao; Liu, Zhensong; Li, Yanbin; Liu, Qian (Frontiers in Marine Science, 2023)
In the Northwest Pacific, a key area for understanding the sources and transport of materials in the ocean, knowledge of the sources, transport, and biogeochemical cycling of trace elements is limited. Trace elements such as the rare earth elements (REEs) can trace the sources and transport of water masses. Here we present dissolved REE concentrations along a longitudinal transect (155oE) from 13°N to 40°N in the Northwest Pacific (≤2000 m). We divided the transect into two subregions: a mixed water region (MWR; 37~40 °N, where the Oyashio and Kuroshio currents mix) and a subtropical region (13~34 °N). In the MWR, REEs were strongly positively correlated with apparent oxygen utilization in subsurface water (depth > the chlorophyll maximum layer, potential density <26.6 kg/m3), with about a 4-fold higher slope (0.15±0.06) than in the subtropical region in subsurface and intermediate waters (0.04±0.003, potential density <27.5 kg/m3). This suggests that REEs are released by organic matter remineralization at a higher efficiency in the MWR vs. in the subtropical region, which can be explained by different water masses and plankton community structures. In addition, we observed a lithogenic input signal of REEs from the Aleutian Islands based on the high La/Yb ratio (>0.35). This ratio was controlled by lateral transport and showed a good agreement with salinity, indicating that it is a useful tracer of low salinity water originating from the subarctic region. Furthermore, we estimated the cross-shelf fluxes of Nd in the Northwest Pacific. The estimated Nd fluxes from the Sea of Okhotsk, the Sea of Japan, the East China Sea, and the South China Sea into the Northwest Pacific were 29~32 t/y, 159~302 t/y, 142~616 t/y, and -298~34 t/y, respectively. This study highlights the importance of considering the cross-shelf REE fluxes in the Northwest Pacific when constructing the oceanic REE budgets.